Efficient screening for ovarian cancers using a combination of tumor markers CA602 and CA546. Issue 1 (1st January 2005) - Saito, M.; Aoki, D.; Susumu, N.; Suzuki, A.; Suzuki, N.; Udagawa, Y.; Nozawa, S.
Abstract : A new efficient screening for ovarian cancer based on a combination of two tumor markers, CA602 and CA546, is reported. These two tumor markers can be detected by a combination immunoenzymometric assay of these two antigens. This combination assay was initially performed in 1189 patients with clinically detected ovarian tumors (final pathological diagnosis: 645 cases of benign disease and 544 cases of malignant disease), and benign disease included 122 patients with endometriosis and 523 normal healthy women. The combination of CA602 and CA546 increased the detection rate of ovarian cancer from 77.8 to 85.8% compared with CA602 alone, demonstrating that the combination assay was effective at detecting ovarian cancers. The combination assay of CA602 and CA546 was then applied to 21, 374 random subjects to screen for asymptomatic ovarian cancer. Ovarian cancer was detected in nine patients (detection rate: 0.04%), of which four cases were stage I disease. A retrospective analysis of these four patients revealed that a screening based on only a single assay would have been negative and further reiterates the effectiveness of this combination assay in detecting potential disease.